(untitled) - Toynbee, Arnold (New York, 1948)
The common aim that runs through this series of papers is to gain some series of insight into the meaning of this mysterious spectacle. The governing idea is the familiar one that the universe becomes intelligible to the extent of our ability to apprehend it as a whole.
Keywords: Civilization,Nền văn minh